THE ROLE OF CUSTOMER EXPERIENCE IN MEDIATING THE INFLUENCE OF SERVICE QUALITY, PLACE IMAGE, AND PROMOTION ON REVISIT INTENTION AT PUMARA BANGKALAN CULINARY CENTER - Ilya Farida; Sri Utami Ady; Nur Sayidah (Universitas 17 Agustus 1945 Surabaya, 2026)
The purpose of this study was to examine the impact of place image, promotion, and service quality on revisit intention at the Pumara Culinary Centre, Bangkalan by using customer experience as the mediating variable. A quantitative approach was employed with an explanatory research design. A total of 150 respondents were chosen by purposive sampling, and the population study consisted of tourists who visited Pumara Bangkalan at least twice. SEM-PLS, or structural equation modeling-based partial least squares, was used to analyse the data. The findings indicated that while promotion had no major impact on customer experience, service quality and place image do. Customer experience, on the other hand, had a favourable and important influence on the intention to revisit. According to analysis mediation, customer experience influenced service quality and place image to revisit intention, However, promotion had a little effect on revisit intention. The results indicated that quality service and the location's image were the major aspects that shape customer experiences and drove return visits. In addition, promotion was unable to generate meaningful emotions in visitors.